2019
DOI: 10.1007/s00167-019-05800-z
|View full text |Cite
|
Sign up to set email alerts
|

Widening of the popliteal hiatus on magnetic resonance imaging leads to recurrent subluxation of the lateral meniscus

Abstract: Purpose This study was undertaken to elucidate the clinical significance of widening of the popliteal hiatus on magnetic resonance imaging (MRI), and to document the clinical results and technical aspects of arthroscopic repair of this finding. Methods Included are 82 knees after arthroscopic surgery, divided according to arthroscopic diagnosis into group A, hypermobility of lateral meniscus, 8 knees; group B, tear of the anterior horn of the lateral meniscus, 32 knees; and group C, no abnormality of the later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Since some studies have reported that the widening of the popliteal hiatus on the MRI leads to a hypermobile lateral meniscus, the opening of the hiatus was also added as an item of evaluation in the current study [ 11 , 16 ]. On proton density-weighted sagittal MRI, Type 1 was defined as no clear high-signal hiatus; Type 2 was defined as a clear high-signal hiatus with a maximum width of 1 mm or less; and Type 3 was defined as a clear high-signal hiatus with a maximum width of 1 mm or more ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since some studies have reported that the widening of the popliteal hiatus on the MRI leads to a hypermobile lateral meniscus, the opening of the hiatus was also added as an item of evaluation in the current study [ 11 , 16 ]. On proton density-weighted sagittal MRI, Type 1 was defined as no clear high-signal hiatus; Type 2 was defined as a clear high-signal hiatus with a maximum width of 1 mm or less; and Type 3 was defined as a clear high-signal hiatus with a maximum width of 1 mm or more ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Once a definitive diagnosis is made, a meniscus suture can be used to treat the condition without symptoms in most cases [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. The hypermobile lateral meniscus is difficult to diagnose using imaging because there is no tear or morphological abnormality of the meniscus itself and it must be diagnosed based on clinical findings alone [ 10 , 11 ]. Although good results can be achieved if the disease is correctly diagnosed, many orthopedic surgeons find it difficult to diagnose; therefore, many patients affected by their symptoms may not receive appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations